Integrated Metabolomics and Proteomics Analysis of Urine in a Mouse Model of Posttraumatic Stress Disorder - Zhou, Daxue; Long, Chengyan; Shao, Yan; Li, Fei; Sun, Wei; Zheng, Zihan; Wang, Xiaoyang; Huang, Yiwei; Pan, Feng; Chen, Gang; Guo, Yanlei; Huang, Yi (Frontiers in Neuroscience, 2022)
Posttraumatic stress disorder (PTSD) is a serious stress disorder that occurs in individuals who have experienced major events. The underlying pathological mechanisms of PTSD are complex, and the related predisposing factors are still not fully understood. In this study, the proteomics and metabolomics characteristics between male the C57BL/6 normal group mice and a PTSD mice model group were analyzed using label-free quantitative proteomics and untargeted metabolomics. Differential expression analysis showed that 12 metabolites and 27 proteins were significantly differentially expressed between the two groups. Bioinformatics analysis revealed that the differentiated proteins were mostly enriched in: small molecule binding, transporter activity, extracellular region, extracellular space, endopeptidase activity, zymogen activation, hydrolase activity, proteolysis, peptidase activity, sodium channel regulator activity. The differentially expressed metabolites were mainly enriched in Pyrimidine metabolism, D-Glutamine and D-glutamate metabolism, Alanine, aspartate and glutamate metabolism, Arginine biosynthesis, Glutathione metabolism, Arginine, and proline metabolism. These results expand the existing understanding of the molecular basis of the pathogenesis and progression of PTSD，but also suggest a new direction for potential therapeutic targets of PTSD. Therefore, the combination of urine proteomics and metabolomics explores a new approach for the study of the underlying pathological mechanisms of PTSD.